Letter (copy) : Spain Campaign Committee - Schevenels, Walther, b. 1894; Gillies, William
029-0060-001 Sent to Adler and Schevenels SPAIN CAMPAIGN COMMITTEE December 31, 1937 I enclose a copy of a telegram with reference to the 7,000 cases of condensed milk which is now en route for Spain on behalf of the 'Milk for Spain' Fund of the Labour Party and the Co-operative Movement. This telegram was sent to-day to the Minister concerned by the Spanish Commercial Attache in London. Mrs. Woods of the Society of Friends, whose address has been given to the Commercial Attache, will be responsible for looking after our interests in Valencia for Madrid. The Asistencia Social will look after their own interests in Barcelona. I have informed Santiago of this arrangement by telegram to-day. In the absence of Mr. Tewson, I have not ventured to make any suggestions with regard to the other food stuffs on this ship which are the property of the International Solidarity Fund. Yours sincerely, WILLIAM GILLIES Secretary, Spain Campaign Committee 292/946/29/60